Heat transfer enhancement with channel surface roughness: A comprehensive review. (June 2022) - Sohal, Abhinav; Kumar, Krishan; Kumar, Rajan
In various applications such as air conditioning, refrigeration, central heating, and chemical processing, heat losses due to thermal resistance are of considerable amount. To improve the thermo-hydraulic performance of the system involved in such applications, it is required to reduce the thermal resistance. This review article focuses on the works related to heat transfer enhancement using two types of surface roughness that are ribs and corrugations. Ribs and corrugations reduce thermal resistance by increasing surface area and creating perturbation in the flow field. This review article covers various experimental, analytical, and numerical studies related to the thermo-hydraulic performance of different working fluids flowing through the channels incorporated with surface roughness. The effects of using different working fluids that are conventional fluids, nanofluids, and hybrid nanofluids on the heat transfer performance of channels with surface roughness are also studied. Authors believe that this article will provide a basis for the advanced research on the thermo-hydraulic performance assessment of the nanofluids and hybrid nanofluids in the ribbed and corrugated channels, which will help in the enhancement of the performance of the system comprising the application of such channels.